Small-scale liquefied natural gas cold utilization systems - Kanbur, Baris Burak (Nanyang Technological University, 2019)
Liquefied natural gas (LNG) import countries have large shares in the global LNG and energy demands; however, large-scale LNG regasification processes can be economically infeasible for the rural and decentralized areas in these countries. In order to increase the feasibility of LNG regasification process, three novel small-scale LNG cold utilization systems are proposed as the single, combined, and carbon dioxide (CO2) reduced-combined systems, respectively. Their performances are compared with the conventional pipeline natural gas-fuelled system. All the proposed systems are evaluated according to the thermodynamic, environmental, economic, thermoeconomic, enviroeconomic, and sustainability aspects. Two new thermoeconomic and enviroeconomic assessment techniques are developed as the life cycle-integrated thermoeconomics (LCiTA) and life cycle-based enviroeconomics, respectively. Two new indices are generated for the different sustainability approaches. Also, the finite sum thermoeconomic approach is developed to investigate the dynamic performance of the proposed systems in the applied environment. Then, the genetic algorithm-based multiobjective optimization is applied by using various objective functions from different perspectives. The thermodynamic results show that the best net power generation rate, thermal efficiency, and exergy efficiency performances belong to the combined system with the average values of 27.95 kW, 71.51%, and 26.48% while the CO2- reduced combined system has the lowest performance with the average values of 24.50 kW, 24.28%, and 69.93%, respectively. The power consumption rate of the LNG pump is found negligible due to its low energy requirement. All the proposed systems are found economically feasible since their payback periods are obtained less than 4 years. According to the environmental assessment, the combined system has the minimum emission rate which presents 7.27% and 10.78% better emission performance than the single and CO2-reduced combined systems, respectively. Although the CO2-reduced combined system mitigates the CO2 emissions roundly by 3.77%, it has the highest emission rate due to the high energy consumption of the compressor during the liquid CO2 capture process. The CO2-reduced combined system presents the lowest thermoeconomic and enviroeconomic performances amongst the other proposed systems. The minimum levelized product cost is found for the combined system with an average of 13.38 $/s. The life cycle-related CO2 emissions are integrated to the thermoeconomics in the LCiTA method, and they cause the levelized product cost increments as 0.5, 0.4, and 0.3 $/s for the single, combined, and CO2-reduced combined systems, respectively. In the componentbased studies, the combustion chamber and the heat exchangers are the most dominant components for the exergy destruction ratio and the levelized destruction costs, while the microturbine components gain significant importance in case of the levelized component costs. The enviroeconomic assessment shows the combined system achieves the minimum environmental payback period with the average value of 2.83 years. By means of the negligible impact of the LNG pump, the single and conventional systems have the same environmental payback periods as 3.06 years. The integration of life cycle-related CO2 emissions increases the environmental payback periods nearly by 100% for all the designs. The combined system has the highest sustainability index with the conventional system. The sustainability index is extended by adding the thermoeconomic parameters, and the new index increases roundly by 1.65 times compared to the conventional sustainability index. On the other hand, the sustainability index of the LCiTA method is found slightly lower than the conventional thermoeconomics due to the integration of life cyclerelated CO2 emissions. The finite sum-based weekly LCiTA performance maps indicate that the levelized product cost and sustainability index achieve their best values during the midday and evening sessions, respectively. In the multiobjective optimization study, the coupled functions present unique best trade-off points, which mean that there is no common optimum point found. Hence, instead of the best trade-off points, the best trade-off region, which covers all the best trade-off points from the different objectives, is suggested for the complex multiobjective optimization studies.